Implementasi Ekonomi Sirkular: Pemanfaatan Larva BSF untuk Pengelolaan dan Peningkatan Nilai Limbah di Perusahaan Pakan - Septiani, Riana; Sundari, Susanti; Lesmana, Nurul Endah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The feed industry faces significant challenges in managing organic waste and ensuring a sustainable supply of animal protein. The implementation of circular economy principles through bioconversion using Black Soldier Fly (BSF) larvae offers an innovative solution to reduce waste while generating high-value biomass. This study aims to evaluate and compare the performance of BSF larvae in processing two types of waste substrates—fish scale waste (P1) and canteen food waste (P2)—to identify the most optimal feeding medium. A quantitative experimental method with a comparative design was conducted within an operational feed production environment. Bioconversion effectiveness was assessed using three key indicators: bioconversion percentage, Waste Reduction Index (WRI), and Feed Conversion Ratio (FCR). The results demonstrated the superior performance of canteen food waste (P2) as a feeding substrate. P2 achieved the highest bioconversion rate at 96.34%, surpassing P1, which reached 78.52%. Additionally, P2 exhibited a faster decomposition rate with a WRI value of 13.98% (P1: 12.79%) and better feed efficiency, as indicated by a lower FCR value (1.04) compared to P1 (1.27). These findings confirm that canteen food waste (P2) provides the most favorable substrate for enhancing BSF larval performance and optimizing organic waste bioconversion.